Pengembangan Model Latihan Serangan Set Plays: Metode Power Play Futsal Pada Pemain Ekstrakurikuler Sekolah Menengah Atas - Argam, Surya; Hidayat, Arif; Endrawan, I Bagus; Satria, M. Haris; Alfani, Rendi (Jurnal Ilmiah STOK Bina Guna Medan, 2025)
The process of providing superior tactics in an effort to provide resistance is a concept of the goal to get a brilliant achievement. With quality tactics, it will be easier for players to excel in a match, one of which is using power play attack techniques. This study aims to find out and identify whether the Set Plays attack training model through Power Play can increase the playability index of Palembang High School futsal players. The research method used is to use R&D to produce a specific product, and test the effectiveness of that product. after the percentage, in the small group trial it was 90% while in the large group trial the percentage was 95%, which can be seen by the increase in the percentage before the small revision and after the product revision. Then based on the results of the percentage in the coach validation, a result of 92.5% "Very Good", This shows that the subjects studied, futsal extracurricular students at SMA Negeri 8 Palembang and SMA Negeri 9 Palembang, have experienced a significant increase since the application of the Practice Model of Attack Set Plays through power Play in futsal games in high schools in the city of Palembang. The implication of this study lies in the provision of optimal tactical stimulus. So that it can be used as a reference by coaches in providing more optimal game quality.